Serum IFN‐γ Predicts the Therapeutic Effect of Mesenchymal Stem Cells Transplantation in Systemic Lupus Erythematosus Patients. (29th July 2017) - Wang, Dandan; Wang, Shiying; Huang, Saisai; Zhang, Zhuoya; Yuan, Xinran; Feng, Xuebing; Lu, Liwei; Sun, Lingyun
Abstract: Umbilical cord (UC)‐derived mesenchymal stem cells (MSCs) show immunoregulatory properties on various immune cells and display therapeutic effects on various autoimmune diseases such as systemic lupus erythematosus (SLE). The aim of this study was to investigate the effect of the SLE environment on UC MSCs and to identify a potential serum biomarker to predict the therapeutic effect. UC MSCs were cocultured with peripheral blood mononuclear cells (PBMCs) from active lupus patients, and the proliferation, apoptosis and surface markers of UC MSCs were observed. UC MSC functional molecules were assessed by real‐time polymerase chain reaction, and the signaling pathways were analyzed by Western blot. The clinical effect of MSC transplantation (MSCT) for lupus patients was followed‐up, whereas baseline serum cytokines were analyzed by enzyme‐linked immunosorbent assay. The coculture of PBMC from lupus patients promoted MSC proliferation. Lupus PBMCs were more potent in stimulating UC MSCs to secrete vascular endothelial growth factor (VEGF) and CXCL‐12. Furthermore, lupus PBMCs activated Akt, IκB, and Stat5 signaling pathways in UC MSCs but did not affect Erk1/2 and Smad1/5/8 pathways. Moreover, our clinical study showed that higher baseline levels of IFN‐γ might predict a good response to MSCT in active lupus patients. Baseline IFN‐γ levels may predict clinical response to MSC therapy for active lupus patients, which will help to choose suitable patients for clinical transplantation.Stem Cells Translational Medicine 2017;6:1777–1785 Abstract : Inflammatory environment in systemic lupus erythematosus patients activate mesenchymal stem cells and initiate the immunoregulatory function.